Social Networks as the Environment Education - Czupryński, Wojsław (Studia Warmińskie, 2016)
The emergence of the global Internet has changed the way the entire human population communicates. The internet has become a platform, where human societies build their lives, and traditional communication over the last few years has been replaced by social networks. Today, social networks are the subject of many debates concerning their advantages, disadvantages and the ideas of what they bring to the future. Portals are not only the way of communication, fun, an idea to spend free time, but also source of social and humanistic knowledge too. Against that, social media could be a huge risk for those who use them. The assigned job above discusses about the topic the detrimental effect what the social networks bring. A series of deviant behaviors caused by use of the portal is also presented in this report. Often they become a dysfunctional generator of actions that manifest themselves among the youth. Consequently, there was a need to take action to stop the growth of this phenomenon among young people. First of all the primary activities at this level are prevention and education in the family.